Performance and suggested alternative strategies in developing Indonesian cocoa export business - Bambang Dradjat; Herman Herman (Indonesian Coffee and Cocoa Research Institute, 2009)
This research focussed on the export development of cocoa bean with respect to its export growth, values and competitiveness. Based on this deve-lopment, the aim of this research is to propose alternative development strategies of export business for cocoa bean in the future. The Analysis Hierarchie Process (AHP) framework of export business of cocoa bean was arranged consecutively from formulation of focuss or goals, identification of affecting factors and actors, deter mination of actor objectives, and recognition of alternative strategies needed. Each component of goals, factors, actors, objectives, and alternative strategies were valued on the basis of their importance using Saaty scales. Results of interviews with experts were analyzed using AHP technique. The development of cocoa bean export from 2000 to 2006 showed the competitiveness position of Indonesia in the world market was fairly good. In order to increase the growth and values of cocoa bean export, the experts consider the role of government as regulators and facilitators is very important. The government became the main actor for the export development through de/regulation related to the cocoa bean commodity. The objectives of actors could be achieved by combining strategies (i) provision of fund in national and regional budget, as well as other sources (ii) implementation of recomended technologies of cocoa, (iii) acceleration of replanting program, (iv) improvement of research productivity in producing high yielding plant materials, (v) development of transportation facilities from farms to harbours, (vi) development of farmers’ organization and partnerships as well as strategic alliance, and (viii) pests and diseases control. Key words: Cocoa bean, expor, role of government, objectives and strategies.